Using strategy analytics to measure corporate performance and business value creation - Kautish, Sandeep Kumar, 1981- (Advances in business information systems and analytics (ABISA) book series., 2021)
"This book provides concepts of strategic analytics and strategic analytics applications in each area of management i.e. market dynamics, customer analysis, operations, and people management with the goal of presenting best industry practices for turning managers into quantitative analysts or quantitative analysts and finally into expert strategists"--